POTENTIAL PARENTS FOR YIELD AND ITS COMPONENTS IN RABI SORGHUM - V. V. KALPANDE, B. A. SAKHARE, R. B. GHORADE A. P. LAD, (The Bioscan, 2015)
The general combining ability study revealed that among the lines, AKRMS-47 A was the best general combiner for yield per plant (2.91) along with four other component characters i.e. plant height (12.37), number of primaries per panicle (2.93), number of grains per panicle(63.35) and thousand grain weight (2.10). Among the testers, the tester RL-5-1 was the best tester and exhibited significant desirable gca effects for grain yield per plant (7.95) along with component character like plant height (19.45). Second tester Rb-397-2 exhibited the positive significant gca effects for the grain yield per plant (6.36).Third tester AKSV-70 R also showed significant positive gca effects for grain yield per plant (5.35) as well as for number of primaries per panicle (7.25) and 1000 seed weight (2.93).Fourth promising tester was G-45-3-1-1 with positive significant gca effects for grain yield per plant (4.70) as well as for the component traits like number of leaves per plant (0.70), panicle breadth (0.64) and number of primaries per panicle (4.55). This one line and four testers need to be extensively used in crossing programme for development of high yielding rabi sorghum hybrids.